2019
DOI: 10.1002/mdp2.29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatments on pore morphology and microstructure of laser additive manufactured parts

Abstract: The slit‐shaped, lack‐of‐fusion pores (LFPs) persistent in the additively manufactured (AM) metals are detrimental to their fatigue resistance due to the associated stress concentrations at the edges. Postbuild treatments, such as hot isostatic pressing (HIP), are routinely used to eliminate pores resulting in, however, inconsistent improvements in fatigue performance. This work critically examines the effectiveness of HIP to eliminate such pores in AM Ti‐6Al‐4V. In addition, conventional heat treatment (HT) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The red profile (T6 heat treatment) has lower relative frequencies for small pores (<10 lm) than the black one (as-built) and higher relative frequencies for pores with an equivalent diameter >10 lm. The density variation after the T6 heat treatment can caused by the previously discussed phenomena ( Refs 39,40,42). In addition, this variation can also occur due to the microstructural variation taking place during the SHT (Fig.…”
Section: Microstructure and Porosities Before And After Heat Treatmentsmentioning
confidence: 86%
“…The red profile (T6 heat treatment) has lower relative frequencies for small pores (<10 lm) than the black one (as-built) and higher relative frequencies for pores with an equivalent diameter >10 lm. The density variation after the T6 heat treatment can caused by the previously discussed phenomena ( Refs 39,40,42). In addition, this variation can also occur due to the microstructural variation taking place during the SHT (Fig.…”
Section: Microstructure and Porosities Before And After Heat Treatmentsmentioning
confidence: 86%
“…Other authors have shown that with the increase of SHT temperature the gas pressure increases and, if the temperature is able to reduce the yield strength of the material around the pore, it can deform it [9,25]. It is certainly possible to say that the pores may spheroidize to minimize the free surface energy as expressed by the Young-Laplace equation [22]. On the other hand, some other authors do not highlight the variation in density after the T6 HT [60,61].…”
Section: Mechanical Propertiesmentioning
confidence: 98%
“…Moreover, the full-cellular structure of the Si eutectic network in the α-Al matrix that is formed, in addition to the Orowan looping behaviour, make the mechanical properties of the AlSi10Mg SLMed higher than the same casting alloy. As matter of fact, the SLMed samples show YS between 250 and 300 MPa, UTS ≤ 400 MPa and strain at failure ≤7% rather than YS between 90 and 110 MPa and UTS between 190 and 210 MPa of casting alloy [4,8,[19][20][21][22][23][24][25]. Additionally, the use of a preheated build platform usually in the range between 150 and 200 • C can increase the mechanical properties of as-built samples due to the aging phenomena [26].…”
Section: Introductionmentioning
confidence: 99%
“…This is definitely seen to be beneficial and the accepted practice for cast and wrought alloys. However, for materials processed using AM, the benefits tend to be less definitive and have in certain cases been found to have a somewhat limited effect [126][127][128][129][130][131][132][133][134][135][136][137][138].…”
Section: Hot Isostatic Pressing and Heat Treatmentmentioning
confidence: 99%